Tissue Engineering for the Diaphragm and its Various Therapeutic Possibilities – A Systematic Review. Issue 8 (30th April 2022) - Boehm, Agnes K.; Hillebrandt, Karl H.; Dziodzio, Tomasz; Krenzien, Felix; Neudecker, Jens; Spuler, Simone; Pratschke, Johann; Sauer, Igor M.; Andreas, Marco N.
Abstract: Diaphragmatic impairments exhibit high morbidity as well as mortality while current treatment options remain unsatisfactory. Tissue engineering (TE) approaches have explored the generation of an optimal biocompatible scaffold for diaphragmatic repair through tissue decellularization or de novo construction, with or without the addition of cells. The authors conducted a systematic review on the current state of the art in diaphragmatic tissue engineering (DTE) and found 24 articles eligible for final synthesis. The included approaches studied decellularization‐based graft generation (9) and de novo bioscaffold construction (9). Three studies focused on in vitro host‐scaffold interaction with synthesized, recellularized grafts (2) and decellularized extracellular matrix scaffolds (1). Another three studies investigated evaluation tools for decellularization efficacy. Among all studies, recellularization is performed in both decellularization‐based (4) and de novo generated scaffolds (4). De novo constructed biocomposites as well as decellularized and recellularized scaffolds induced pro‐regenerative remodeling and recovery of diaphragmatic function in all examined animal models. Potential therapeutic applications comprise substance defects requiring patch repair, such as congenital diaphragmatic hernia, and functional diseases demanding an entire organ transplant, like muscular dystrophies or dysfunction after prolonged artificial respiration. Abstract : From bench to bedside, this systematic review presents an extensive overview on the current state of the art in diaphragmatic tissue engineering. Characteristics and preclinical implementation of novel decellularization‐based and de novogenerated scaffolds with optional additional recellularization are presented, and their potential therapeutic value in substance and functional diaphragmatic defects is highlighted.